Waḥdat al-Wujūd as Post-Avicennian Thought: Comparing Writings on the Basmala by Ibn ‘Arabī and ‘Abd al-Karīm al-Jīlī - Rüdiger Lohlker (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2021)
The article has a two main aims: situating the (post-)Akbarian ideas in the context of Islamic post-classical, esp., post-Avicennian thought and moving the field of the study ‘Abd al-Karīm al-Jīlī away from the focus on one work, al-Insān al-Kāmil, to the inclusion of a broader specter of writings regarded as minor texts. The article proposes a rhizomatic reading of the sources to re-open the field of analysis. At the same time, the article argues for waḥdat al-wujūd as a main element of post-classical Islamic discourse sharing a framework with post-Avicennian thought. Reconfiguring the field of the study of writings on waḥdat al-wujūd this will allow for an analysis of the field not an analysis of selected works. The analysis will be done by a close reading of a set of works focussed on the basmala as one of the most important formulae. This is not an analysis of the letters and its interpretations but much more of the post-classical philosophy and the relation of the Sufism of waḥdat al-wujūd to it. The article discusses the role of the writings of al-Jīlī and Ibn ‘Arabī. The analysis of the field of writings of al-Jīlī opens a perspective on waḥdat al-wujūd as an interrelated field of meanings beyond the focus on single works and its possible intertextual references.